2021
DOI: 10.48185/she.v2i2.328
|View full text |Cite
|
Sign up to set email alerts
|

Challenges and Opportunities in a Local College in Time of COVID-19 Pandemic

Abstract: The COVID-19 pandemic has presented challenges and opportunities to higher education institutions all over the world. This paper adds to the growing literature on new perspectives in education amidst the global pandemic. It discusses challenges and opportunities in the context of a local higher education institution. Inputs from teaching and non-teaching personnel were considered. Documentary analysis of proposed transition plans and actions plans from the different departments of the college was made. Recomme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…(Student 6: Due to technological issues, she cannot access Moodle, VLE, or any educational platform required for this online learning.) The results also showed that the lack of preparation for online learning was one barrier (Paguio et al, 2021). Some students lack access to laptops or tablets for learning, which explains why they experience higher COVID-19 anxiety associated with the consequences.…”
Section: Technological Issuesmentioning
confidence: 90%
See 1 more Smart Citation
“…(Student 6: Due to technological issues, she cannot access Moodle, VLE, or any educational platform required for this online learning.) The results also showed that the lack of preparation for online learning was one barrier (Paguio et al, 2021). Some students lack access to laptops or tablets for learning, which explains why they experience higher COVID-19 anxiety associated with the consequences.…”
Section: Technological Issuesmentioning
confidence: 90%
“…Indeed, higher education institutions have been compelled to modify and integrate flexible teaching and to learn in response to the COVID-19 pandemic to guarantee the students' academic continuity (Paguio et al, 2021). This educational problem needs to be promptly deliberated upon so that everybody can be delighted in the satisfaction of high-quality pedagogy through technology (Cojocariu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…With this shift in education, various challenges are faced by both teachers and the students. Countermeasures in education are taken to continue education of the student despite the dilemma of the COVID-19 pandemic (Toquero, 2020;Paguio et al, 2021). The study of Barrot, et.al (2021) revealed that the greatest impact of COVID-19 pandemic is on the students' quality of learning and students' mental health.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of innovation is being undertaken by the Philippine Higher Education Institutions (HEIs) to cope and continue education amid the pandemic. Despite of this, the system still faced with various challenges, which according to Joaquin, et.al (2020) and Paguio et al (2021), calls for policy responses among institutions and more learning innovations to lessen the challenges encountered by both teachers and learners. It is true that learners faced several challenges which also include teachers (Asio & Jimenez, 2021b) during the pandemic but several studies provide that students are motivated to pursue studies.…”
Section: Introductionmentioning
confidence: 99%
“…With these, teachers expect to submerge to capacity buildings, training workshops, coaching-mentoring, and even peer tutoring, to better capture the core of changes with the mission of wholeheartedly serving our country's clients. Some of the challenges [14] are the different platforms or alternative modes [15] of engaging the teaching and learning will be combined. The schedule will be flexible [16], and the decreased number of learners per class must be addressed before the next standard starts this 2022.…”
Section: Introductionmentioning
confidence: 99%